Claus Bjørn, Grundtvig som politiker - Udgivet af Thorkild C - Wåhlin, Vagn (Grundtvig-studier, 2009)
Claus Bjørn, Grundtvig as politician - published by Thorkild C. Lyby Reviewed by Vagn Wåhlin and Kim Arne Pedersen